2006
DOI: 10.1097/01.blo.0000224052.01873.20
|View full text |Cite
|
Sign up to set email alerts
|

Unicompartmental or Total Knee Arthroplasty?

Abstract: There are few direct comparative studies evaluating results after unicompartmental knee arthroplasty and total knee arthroplasty. We determined the active range of motion, Knee Society score, and 5-year survivorship rate after 54 consecutive unilateral unicompartmental knee arthroplasties compared with a matched group of 54 unilateral total knee arthroplasties. The two groups of patients were matched for age, gender, body mass index, preoperative active range of movement, and preoperative Knee Society scores. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(67 citation statements)
references
References 30 publications
2
63
1
1
Order By: Relevance
“…Proposed advantages of UKA over TKA include both technical factors (less invasive surgery, preservation of bone stock, comparative ease of revision) [5,32,37,41,56] and improved clinical outcomes (superior knee kinematics, less blood loss, faster recovery, shorter inpatient stay) [4, 20-22, 25-27, 50, 62]. Clinical outcome scores have previously focused on absolute values at preoperative and postoperative review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed advantages of UKA over TKA include both technical factors (less invasive surgery, preservation of bone stock, comparative ease of revision) [5,32,37,41,56] and improved clinical outcomes (superior knee kinematics, less blood loss, faster recovery, shorter inpatient stay) [4, 20-22, 25-27, 50, 62]. Clinical outcome scores have previously focused on absolute values at preoperative and postoperative review.…”
Section: Discussionmentioning
confidence: 99%
“…TKA, including minimal access surgery, preservation of bone stock, and ease of revision [5,32,37,41,56], as well as superior knee ROM and kinematics, less blood loss, faster recovery, and a decreased hospital admission [4, 20-22, 25-27, 50, 62]. Satisfaction after either TKA or UKA is similar [54].…”
Section: Introductionmentioning
confidence: 99%
“…Use of unicompartmental knee arthroplasty (UKA) has increased considerably in recent decades as a result of improved implant technology and surgical techniques [3,28]. It has been suggested that UKA should result in a more normal restoration of knee function compared with TKA because the procedure requires less soft tissue dissection and both cruciate ligaments are preserved [7,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on survival rates and clinical measures (eg, Knee Society scores) of UKA demonstrate mixed results [3,12,15,28,30], and some evidence of early failure rates has been reported [21]. Therefore, some surgeons are reluctant to use this procedure as a result of conflicting evidence of effectiveness [3,12,15,28,30].…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of isolated unicompartmental knee osteoarthritis, many surgeons elect to perform UKA citing its potential benefits, including decreased operative time, smaller incision, less aggressive bony resection, preservation of cruciate ligaments, improved range of motion, shorter hospital length of stay, decreased morbidity and mortality, and its preserved knee kinematics [2,15,22,23,26,36]. Despite these benefits, there appears to be conflicting reports in the literature with regards to the long-term survival of UKA implants; with registry data demonstrating increased rates of revision compared to TKA [20,21,28], while case series demonstrate equivalent outcomes [5,10,16,17,25,27,30,32,34].…”
Section: Introductionmentioning
confidence: 99%